Pengaruh Modifikasi Tepung Okara melalui Fermentasi: Perbandingan Metode fermentasi dan Lama Inkubasi terhadap Sifat Fisikokimia: Fermentation Methods and Incubation Time: Their Effects on the Physicochemical Properties of Modified Okara Flour - Rasmiyana Rasmiyana; Ade Galuh Rakhmadevi; Frengky Hermawan Hadi Prasetyo; Putu Tessa Fadilah; Putri Satika Dewi (Jurnal Teknologi dan Mutu Pangan, 2026)
Okara, a by-product of soy milk and tofu production, is rich in fiber but is underutilized. One way to use okara is to convert it into flour for use as an ingredient in cookie production. This research aims to evaluate the effects of fermentation type and duration on the physical and functional properties of okara flour. The research used a Completely Randomized Design (CRD) with two factors: fermentation type (spontaneous, commercial yeast A, commercial yeast B) and fermentation duration (48 and 72 hours). The fermented okara was dried and analyzed for moisture, ash, solubility, and swelling power. The results showed that the type and duration of fermentation had a significant effect (p<0.05) on moisture content, ash content, and solubility, but did not affect swelling power (p>0.05). Fermentation with commercial yeast A for 48 hours (F2W1) yielded the highest solubility (39.87%), while spontaneous fermentation for 48 hours (F1W1) resulted in the lowest  oisture content (0.91%). All treatments produced a moisture content that meets the Indonesian National Standard (SNI) for wheat flour. It can be concluded that fermentation with yeast A and a 48-hour incubation period yields the best profile, as it shows the highest solubility. Consequently, it has the potential to be developed as a raw material for cookie production.